Search for the decay of the Higgs boson to charm quarks with the ATLAS experiment - Aaboud, Morad; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Britzger, Daniel; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physical review letters, 2018)
A direct search for the standard model Higgs boson decaying to a pair of charm quarks is presented. Associated production of the Higgs and Z bosons, in the decay mode ZH→ℓ+ℓ−c¯c is studied. A data set with an integrated luminosity of 36.1 fb−1 of pp collisions at √s=13TeV recorded by the ATLAS experiment at the LHC is used. The H→c¯c signature is identified using charm-tagging algorithms. The observed (expected) upper limit on σ(pp→ZH)×B(H→c¯c) is 2.7 (3.9+2.1−1.1) pb at the 95% confidence level for a Higgs boson mass of 125 GeV, while the standard model value is 26 fb.
M. Aaboud, A.E. Bolz, A.E. Baas, O. Brandt, D. Britzger, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, K. Meier, H. Meyer Zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S.M. Weber, J. Wang, M. Wessels [und weitere] (ATLAS Collaboration)
Gesehen am 17.04.2019